2006
DOI: 10.2140/pjm.2006.227.151
|View full text |Cite
|
Sign up to set email alerts
|

The tangent grupoid of a Heisenberg manifold

Abstract: RAPHAËL PONGEAs a step towards proving an index theorem for hypoelliptic operators on Heisenberg manifolds, including for those on CR and contact manifolds, we construct an analogue for Heisenberg manifolds of Connes' tangent groupoid of a manifold. As is well known for a Heisenberg manifold (M, H) the relevant notion of tangent bundle is rather that of a Lie group bundle of graded 2-step nilpotent Lie groups G M. We define the tangent groupoid of (M, H) as a differentiable groupoid Ᏻ H M encoding the smooth d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 17 publications
(60 reference statements)
1
38
0
Order By: Relevance
“…This isomorphism commutes with the dilations in (2.4) and it can be further shown that it gives rise to a Lie group isomorphism from GM onto GM (see [50]). For a ∈ U we let ψ a : R d+1 → R d+1 denote the unique affine change of variable such that ψ a (a) = 0 and (ψ a ) * X j (0) = ∂ ∂x j for j = 0, .…”
Section: Heisenberg Manifoldsmentioning
confidence: 86%
See 2 more Smart Citations
“…This isomorphism commutes with the dilations in (2.4) and it can be further shown that it gives rise to a Lie group isomorphism from GM onto GM (see [50]). For a ∈ U we let ψ a : R d+1 → R d+1 denote the unique affine change of variable such that ψ a (a) = 0 and (ψ a ) * X j (0) = ∂ ∂x j for j = 0, .…”
Section: Heisenberg Manifoldsmentioning
confidence: 86%
“…Next, the terminology Heisenberg manifold stems from the fact that the relevant tangent structure in this setting is that of a bundle GM of graded nilpotent Lie groups (see [1,3,19,23,27,50,56,64]). This tangent Lie group bundle can be described as follows.…”
Section: Heisenberg Manifoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Heisenberg calculus was developed by Folland-Stein [12] and Taylor [23] in the 1970s. An adaptation of the tangent groupoid to the Heisenberg calculus was developed in [8,21], which led to the index theorem for the Heisenberg calculus [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…A deformation groupoid taking into account this inhomogeneous calculus was constructed independently in ( [98,25,27,26]) and [111,70,113]. Both these constructions are rather technical and based on higher jets.…”
Section: Inhomogeneous Pseudodifferential Calculusmentioning
confidence: 99%